Empagliflozin in Patients With Heart Failure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Pan, Deng; Xu, Lin; Chen, Pengfei; Jiang, Huiping; Shi, Dazhuo; Guo, Ming (Frontiers in Cardiovascular Medicine, 2021)
Purpose To evaluate the effect of empagliflozin in patients with heart failure and reduced ejection fraction (HFrEF). Method We performed a systematic search of PubMed, EMBASE, and the Cochrane Library database through January 20, 2021. Randomized controlled trials (RCTs) were included that compared empagliflozin and placebo in patients with heart failure and reduced ejection fraction. Dichotomous variables were expressed as risk ratio (RR) with 95% confidence intervals (CIs). Continuous variables were calculated and expressed by mean differences (MD) and standard deviation (SD). Meta-analysis was conducted using a random-effects model on outcomes with high heterogeneity. Results 7 studies were included in our meta-analysis (n=5150). Significant difference was observed in the composite of cardiovascular deaths and heart failure hospitalizations (RR: 0.72 (95% CI, 0.62-0.84); I2= 5%; P< 0.0001), heart failure hospitalizations (RR: 0.67 (95% CI, 0.56-0.80); I2= 0%; P< 0.0001), change of Kansas City Cardiomyopathy Questionnaire (KCCQ) score (MD: 1.70 (95% CI, 1.67-1.73); I2= 0%; P< 0.00001) and body weight (MD: -1.43 (95% CI, -2.15- -0.72); I2= 84%; P< 0.0001) from baseline. Whereas empagliflozin didn’t show better in change of 6-minute walk test (6MWT) (MD: 34.06 (95% CI, -29.75-97.88); I2= 97%; P= 0.30) and NT-proBNP (MD: -98.63 (95% CI, -225.83-29.11); I2= 68%; P= 0.13) from baseline. Conclusion The findings suggest that empagliflozin was effective in reducing cardiovascular deaths and heart failure hospitalizations. Further well-designed RCTs are needed to evaluate the long-term effect pf empagliflozin in patients weth HFrEF.